Non-Governmental Organizations Serving Farmworkers in Florida - Carlene Thissen; Fritz Roka (EDIS)
FE836, a 15-page fact sheet by Carlene Thissen and Fritz Roka, is a compilation of the non-governmental organizations that serve farmworkers in Florida. Published by the UF Department of Food and Resource Economics, July 2010.